The afterlife of interviews: explicit ethics and subtle ethics in sensitive or distressing qualitative research. (October 2022) - Pascoe Leahy, Carla
When conducting interviews about sensitive subject matter such as family life, powerful emotions may arise. The kinds of unexpected distress that can surface in interviews concerning topics laden with personal significance are different to the readily anticipated trauma that accompanies interviews in post-crisis or post-conflict situation. This article analyses the ethical considerations that accompany such research, drawing upon literature from oral history and qualitative sociology. The article traces ethical issues during the temporal phases of qualitative research – before, during and after an interview – before proposing three strategies that interviewers can adopt to help protect narrators from ongoing harm or distress after an interview. Such ethical safeguards include the self-interview, the post-interview follow-up with the narrator, and adopting an ethics of reciprocity that allows the narrator to feel that they are contributing to a larger purpose through involvement in research.